Interoperability, safety and security in IoT : second International Conference, InterIoT 2016 and third International Conference, SaSeIoT 2016, Paris, France, October 26-27, 2016, Revised selected papers /: second International Conference, InterIoT 2016 and third International Conference, SaSeIoT 2016, Paris, France, October 26-27, 2016, Revised selected papers. (2017) - Unknown
No abstract available